Power and old age. The stories and their policies - Iacub, Ricardo (Revista Kairós-Gerontologia, 2015)
This article identifies and critically analyzes three metanarratives and their central representations of aging and old age: life course and its decline; temporality, the end of life, prejudice and ageism. We will analyze the interconnection between the levels of the narratives and how great narratives help in the building of policies for the elderly, social practices and conceptual metaphors. Finally, the concept of "alternative narratives" that questions and promotes differences in the production of stories and metaphors will be proposed.